Radiological and Functional Outcomes of External Fixation in Osteoporotic Proximal Humerus Fractures at a Tertiary Care Hospital: External Fixation for Osteoporotic Humerus Fractures - Sabir, Kamran; Haq, Farman Ul; Ikram, Muhammad; Naseer, Zain; Altaf, Waheed; Asfandyar, .; Saddiq, Sadaf; Khan, Zairmal (Pakistan Journal of Health Sciences, 2025)
Treatment of humeral shaft fractures typically involves conservative methods or surgical options like plating and intramedullary nailing, each with limitations. External fixation, allowing for adjustable reduction and early mobilization, has emerged as a promising alternative. Objectives: To assess external fixators’ functional and radiological outcomes in patients with humeral shaft fractures at a tertiary care hospital. Methods: This quasi-experimental study included 60 patients meeting the inclusion criteria enrolled from the Department of Orthopedic Surgery, Ghurki Hospital, Lahore. External fixators were applied under fluoroscopic guidance, with two half-pins inserted proximally and distally to stabilize the fracture. Patients were followed up at 4, 6, and 12 weeks post-surgery, with functional outcomes evaluated at 12 weeks using the University of California, Los Angeles (UCLA) rating scale. Results: The patient cohort was predominantly male (83.3%), with a mean age of 40.25 ± 11.54 years. The mean duration of fracture before treatment was 4.4 ± 2.38 days. Fractures were nearly evenly distributed between the left (48.3%) and right (51.7%) sides. Road traffic accidents were the primary cause of injury (66.7%). The mean UCLA score at 12 weeks was 30.30 ± 3.32, with 52 patients (86.7%) achieving satisfactory outcomes and 8 (13.3%) experiencing unsatisfactory results. The patients reached radiological union at an average of 10.5 ± 1.9 weeks. Conclusions: The results of our study demonstrate that external fixation is a feasible option for treating proximal humerus fractures, improving both functional and radiological outcomes. While reducing surgical difficulties, the suggested method increases fixation stability.